Law Enforcement and Human Rights Protection in Public Administration: A Qualitative Approach to the Implementation of Public Policy - Fatmawati A Rahman; I Gede Arya Pering Arimbawa; Rostini Rostini; A Fadel Muhammad (Jurnal Ilmiah Ilmu Administrasi Publik, 2024)
This research investigates the relationship between law enforcement and the protection of Human Rights in the context of public administration in Indonesia. Qualitative research methods were used to gain a deep understanding of policy implementation and the interaction between law enforcement and human rights protection. Data were collected through in-depth interviews with government officials, human rights activists, academics, and community members directly affected by public policies. The findings indicate that law enforcement continues to face significant challenges such as lack of resources, low institutional capacity, and corruption practices. On the other hand, while there have been improvements in recognizing basic rights, complexities remain in human rights protection, particularly concerning discrimination and abuse of power by authorities. Research recommendations suggest strengthening institutional legal capacity, enhancing transparency, fostering more active community participation, and engaging in cross-sector dialogues to strengthen fair law enforcement and inclusive human rights protection in public administration.